Dilatatone, a new chlorinated compound from Parmotrema dilatatum. Issue 21 (2nd November 2021) - Phan, Hoang-Vinh-Truong; Devi, Asshaima Paramita; Le, Hoang-Duy; Nguyen, Thanh-Trung; Nguyen, Huu-Hung; Le, Tran-Thai-Duong; Nguyen, Tai Hoang; Sichaem, Jirapast; Duong, Thuc-Huy
Abstract: Chemical investigation of the lichen Parmotrema dilatatum led to the isolation of a new chlorinated compound, named dilatatone (1 ), along with a known compound, sernanderin (2 ). Their chemical structures were determined by analysis of their 1 D and 2 D NMR spectra, HRESIMS, and ECD data. Both compounds showed weak α- glucosidase inhibitor activity. Graphical Abstract: